Penerapan Kesehatan dan Keselamatan Kerja (K3) Siswa di Workshop Tata Kecantikan Rambut SMK NEGERI 7 Padang - Monysa, Monysa; Rahmiati, Rahmiati; Astuti, Murni (Journal of Home Economics and Tourism, 2016)
The research was motivated from the phenomenon that shows their negligence in the application of health and safety at work in students pdang in practice in the workshop which can cause accidents. This study aims to describle the implementation of the health and safety of students against themselves, against pelalatan work and the working environment in implementing the practice i hairstyling workshop smk 7.This type of research is quantitative descriptive. Populasi was grade 1,2,3 which amounted to 102 people,sample amounted to 51 people, Research instruments using a questionnaire with a scale of 1 to 4 in the form of positive and negative statements, data collection techniques are in the form of aquestionnaire, test instruments performed on a population that does not include the sample of 30 people, engineering data analysis and categorization percentage formula.The results showed that the average level of attainment of respondents on the application of K3 personal hygiene private student loans.52 with very low category and cleanlinessof working clothes at 54 with very low category, the application K3 to the use of tools and equipment used when practice for 63 whith low category, with descriptions that application of the use of the tool by 62 with low category and how the storage of tools and equipment amounted to 65 with moderate category, application k3 in today’s working enviromment practices by 56 with low category, the description that the air vent has a percentage of the result by 56, lighting has a percentage of 58, sanitation has a percentage of 56. The floor has a percentage of 56, has a percentage of electricity 54, and fire hazards has a percentage of 56, all the sub-indicators with low category. Results suggested that student improve their know ledge of the dangers that can occur if you do not apply the health and safety at work well and benefit in implementing occupational health and safenty in the workshop.Kata Kunci: Kesehatan dan Keselamatan Kerja, Workshop1Mahasiswa